ANTECEDENTS AND CONSEQUENCES OF TRANSACTION EXPERIENCE AMONG USERS OF QRIS BASED DIGITAL PAYMENT SYSTEMS IN INDONESIA - Erditia, Vionyka Amanda; Luki Adiati Pratomo (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2026)
This research seeks to investigate the factors that shape and the outcomes driven by transaction experience among users of QRIS-based digital payment platforms in Indonesia. More precisely, it explores how four key perceptions influence transaction experience: the perceived inefficiency of using cash, the perceived health risks associated with cash, the perceived convenience of cashless payments, and the perceived security and privacy of cashless transactions. Additionally, the study assesses how transaction experience, in turn, affects users’ behavioral intention to continue using such digital payment systems Adopting a quantitative methodology, the study utilizes SEM for data analysis. The data were analyzed with SPSS version 21 and AMOS version 23, and collected through purposive sampling from individuals who actively use QRIS in Indonesia. Findings reveal that all four antecedent variables significantly and positively influence transaction experience. Moreover, transaction experience itself exerts a significant positive effect on users’ behavioral intention to engage with QRIS-based payment systems in the future.